Символизм в системе культуры - Карпенко, А.В. (Культура народов Причерноморья, 2002)
В статье рассматривается один из самых важных концептов философской современной мысли – символ. Опираясь на фактический материал, была дана попытка определить, что такое символизм, и какова его роль в становлении ряда философско-культурологических и эстетических течений конца 19 – начала 20 века. The author is studying one of the most important concepts of the modern philosophic and aesthetic thought – symbol.
Leaning on the given material the author tried to determine the concept of symbolism and its role in the making of a number of philosophic, cultural and aesthetic currents at the close of the 19-th and at the beginning of the 20-th century.